Characteristics and Typology of Kyai Leadership Within Pesantren - Sarwadi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
This article attempts to explore types and characteristics of Kyai leadership within Pesantren. This library research found that there are 412 articles related to the leadership of Kyai. Based on the inclusion criteria, there are 12 articles yielded as the material sources. The appropriate data found in the searching machine is analyzed accordingly to the research questions by employing a qualitative approach. Specifically, the types of Kyai leadership within Pesantren are charismatic, transformative, and democratic leaderships. The characteristics of Kyai leadership in Pesantren including having a strong and authoritative leadership character in maintaining Pesantren’s education and development; keeping the traditions, local principles and interacting with global values; having internal and external networks e.g a genealogical, ideological, historical, intellectual, theological, and spiritual networks in serving Islam and Indonesia. This research recommends for further researchers to address this study focuses on a networking of Kyai. The themes of Kyai’s intellectual networks, ideological networks, spiritual networks, theological network are highly recommended.